Synthesis and Characterization of Hyper‐Branched Nanoparticles with Magnetic and Plasmonic Properties. Issue 26 (11th July 2022) - Candreva, Angela; Parisi, Francesco; Bartucci, Rosa; Guzzi, Rita; Di Maio, Giuseppe; Scarpelli, Francesca; Aiello, Iolinda; Godbert, Nicolas; La Deda, Massimo
Abstract: Hybrid nanoparticles, composed of an iron oxide magnetic core embedded with gold fractal‐grown hyper branches, have been synthesized by a seed‐mediated growth approach. Magnetic and plasmonic properties have been described respectively through ferromagnetic resonance (FMR) and extinction spectra. According to the hydroxylamine amount, used as a surface catalysed reducing agent, the number of branches and the intensity of the fractal growth have been finely tuned and were observed through TEM microscopy. The magnetic core allowed their motion control via an external magnetic field. The plasmonic properties of these hyper‐branched hybrid nanoparticles were recorded similar to those shown by the branched gold nanoparticles, but it is interesting to note that they showed an encouraging photothermal response. Abstract : A synthetic strategy has been finely performed to obtain hybrid iron oxide/gold hyper branches nanoparticles with magnetic and plasmonic behaviours by the use of hydroxylamine as a surface‐catalysed reducing agent.